Intersections of the Right to Education and Human Dignity in International Human Rights Law: A Purpose-Based Analysis - Obinna Christian Edeji (Laws, 2025)
The atrocities of World War II were pivotal to the launch of the human rights project, which became anchored on the recognition of the inherent dignity of all humans and formed a cornerstone justifying the ascription of rights. Indeed, it became essential to recognise education as a human right given the emergent need to promote the use of reason, having recognised humans as people imbued with inherent dignity. This paper explores the right to education in international human rights law (IHRL) from the perspective of its purpose, and uses IHRL as its starting point. It argues that the ascription of inherent dignity to everyone justifies access to education and investigates the nexus between dignity and education, arguing that access to education is a sine qua non to expanding the inherent dignity of all humans. Thus, it argues that the recognition of dignity requires that all children must be provided with equal access to education to stimulate the use of reason.